2012
DOI: 10.3386/w17965
|View full text |Cite
|
Sign up to set email alerts
|

Why is the Teen Birth Rate in the United States so High and Why Does it Matter?

Abstract: for helping to shape this article. Any views expressed are those of the authors alone. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 29 publications
(30 reference statements)
5
148
0
Order By: Relevance
“…Neither pronatalist nor antinatalist policies are popular in the United States, suggesting that policymakers do not have strong opinions about the current overall fertility rate. By contrast, the U.S. teen fertility rate is the highest in the developed world (Kearney and Levine 2012), and policymakers of all political persuasions generally agree that teen fertility should be reduced. Although recent research argues that teen fertility is a symptom rather than a cause of disadvantage (Kearney and Levine 2012), disagreement on this point remains, and concerns about the impact of having a teen mother on child outcomes persist (National Campaign to Prevent Teen and Unplanned Pregnancy 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither pronatalist nor antinatalist policies are popular in the United States, suggesting that policymakers do not have strong opinions about the current overall fertility rate. By contrast, the U.S. teen fertility rate is the highest in the developed world (Kearney and Levine 2012), and policymakers of all political persuasions generally agree that teen fertility should be reduced. Although recent research argues that teen fertility is a symptom rather than a cause of disadvantage (Kearney and Levine 2012), disagreement on this point remains, and concerns about the impact of having a teen mother on child outcomes persist (National Campaign to Prevent Teen and Unplanned Pregnancy 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These types of changes have been linked to increased teen sexual activity (Buhi and Goodson 2007;Carpenter 2005;Kirby 2001a;Vesely et al 2004). Moreover, Kearney and Levine (2012) argued that U.S. teens exhibit higher fertility when they face greater "despair" about the prospects of advancing economically.…”
Section: Introductionmentioning
confidence: 99%
“…Among urban youth, teenage pregnancy is more normative due to its higher rates [28]. These negative outcomes are further compounded in metropolitan areas by elevated rates of poverty, incarceration, dense sexual networks, discrimination, racial segregation, and lack of health insurance and regular sources of care [1,9,22,50].…”
Section: Introductionmentioning
confidence: 99%
“…Early research supported a commonly held notion that teenage pregnancy leads to adverse outcomes, particularly in the areas of education, employment, and marriage (Card and Wise, 1978;Grogger and Bronars, 1993). However, recent studies employing more-rigorous methods have shown that at least a portion of these effects, in fact, may not be causally related to the pregnancy itself, but instead may be due to the disadvantaged socioeconomic circumstances of the teenagers when they become pregnant (Hotz, McElroy, and Sanders, 2005;Kane, Morgan, Harris, and Guilkey, 2013;Kearney and Levine, 2012;Levine and Painter, 2003). As a result, there is a growing consensus that the adverse effects directly attributable to teen pregnancy may be less than originally believed, particularly in the long term.…”
Section: Previous Research On Cas-carrera Pregnancy Prevention Programsmentioning
confidence: 93%